Surface studies of thin films with a focus on potentially protective films on vanadium - Asunskis, Daniel John (Kansas State University, 2005)
Thin films can be created on the surface of a metal, protecting it from oxidation and corrosion. Phosphate films have historically been a common choice for these corrosion resistant films. In this dissertation, the oxidation of vanadium metal by water and atmosphere is studied. Also, a series of phosphate films on the surface of vanadium metal were created and are studied as potential corrosion resistant films. Lastly, an independent study identifying the oxidation state of copper in a biological sample is carried out. To characterize these thin films, X-ray Photoelectron Spectroscopy (XPS) is employed. The reaction of vanadium metal with the atmosphere and distilled, de-ionized, water is studied. The core level and valence band results are explored and compared to calculated valence band spectra for some vanadium oxides. The etching of vanadium metal and reaction of the etched metal with a phosphoric acid solution are studied. Synthesized vanadium phosphate compounds serve as model compounds for the analysis of a phosphate coating created on the surface of vanadium metal by the reaction of vanadium metal with phosphoric acid by a newly developed bench top method. The core level and valence band regions for the compounds and coating are discussed along with cluster and band structure calculations for interpretation. The variation in the coating on vanadium metal by biasing the metal at different potentials during reaction is also studied. Coatings are also created on vanadium metal using different forms of phosphorus oxy-acid. An analysis of the various coatings is performed by XPS and accompanied by predictive calculations. In an additional study, the oxidation state of copper in a biological compound is identified. The analysis makes use of satellite features commonly seen in XPS to make the determination. A discussion of the origin of these features and the energy of the shifts is given, along with the results for the other core level XPS regions for the compound.
Keywords: XPS; Vanadium; Vanadium phosphate; Chemistry, Analytical (0486)